Потенціал та досягнення вузівської науки України - Ісакова, Н.Б. (Наука та наукознавство, 2017)
Стаття присвячена проблемі внеску вищих навчальних закладів у наукові досягнення України та їх ролі у національній інноваційній системі. На базі огляду наукових публікацій, аналізу статистичних даних Держстату України, вітчизняних та міжнародних рейтингів університетів виявлено основні тенденції, що склалися на сьогодні у науковому секторі вищої освіти України. З’ясовано, що попри досягнення у реформуванні освітньої складової вищої школи, існують чималі проблеми ефективного використання наукового потенціалу ВНЗ. За винятком окремих випадків, вищі навчальні заклади України не відповідають сучасним вимогам до так званих дослідницьких та підприємницьких університетів, незважаючи на те, що кільком з них надано статус дослідницького університету. Наука ВНЗ України залишається здебільшого поза світовими рейтингами університетів та є слабо інтегрованою у світовий науково-технологічний простір. Статья посвящена проблеме вклада высших учебных заведений в научные достижения Украины и их роли в национальной инновационной системе. На базе обзора научных публикаций, анализа статистических данных Госстата Украины, отечественных и международных рейтингов университетов определены основные тенденции, сложившиеся на сегодня в научном секторе высшего образования Украины. Выявлено, что несмотря на достижения в реформировании образовательной составляющей высшей школы, существует немало проблем эффективного использования потенциала вузовской науки. За исключением отдельных случаев, высшие учебные заведения Украины не соответствуют современным требованиям, которые предъявляются к так называемым исследовательским и предпринимательским университетам, несмотря на то, что 14 вузам был присвоен статус исследовательского университета. Вузовская наука Украины остается по большей части вне мировых рейтингов университетов и слабо интегрированной в мировое научно-технологическое пространство. The article deals with the problem of contribution from higher education institutions to the Ukrainian scientific achievements and the roles of universities in the national innovation system. The article is based on the review of scientific publications; analysis of data of the State Statistics Service of Ukraine, and analysis of the national and international rankings of universities. Major current trends in the scientific sector of higher education in Ukraine are identified. It is revealed that, although some progress in the reform of the educational component of universities has been achieved, the problem of research activities in universities and effective use of scientific potential of the higher education institutions remains in place. Except for rare cases, Ukrainian universities do not meet the modern requirements to «research universities» and «entrepreneurial universities », despite the fact that 14 institutions have been granted the «Research University» status of by the Ministry of Education and Science of Ukraine. Research performed in the universities of Ukraine is mostly outside the university world rankings and is poorly integrated into the global scientific and technological area.